Creationism and Anti-Creationism in the United States A Sociology of Conflict - Kaden, Tom.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book deals with professional creationist and anti-creationist organizations in America, and describes how the "conflict between science and religion" is the result of the interaction between these two groups. It retraces their history from the 1960s onwards, and identifies crucial turning points that led to new forms of creationism and anti-creationism. It explains their strategies, labels and arguments as effects of this history and structure. Taking a field theoretical approach, the book avoids problems of prior creationism research, making it possible to identify the mechanisms through which creationism generates new strategies, arguments, and media output. The field model is used as an interpretive tool to make sense of some of the most important creationist and anti-creationist publications and media statements.
Chapter 1. Introduction: Creationism in the United States of America: An Exposition -- Chapter 2. Creationist Positions -- Chapter 3. Creationist Organizations and Their Modes of Action -- Chapter 4. Anti-Creationism in the United States -- Chapter 5. "Science" and "Religion": The Impasse of Creationism Research -- Chapter 6. A Field Theory of Creationism and Anti-Creationism -- Chapter 7. Creationist and Anti-Creationist History Constructs -- Chapter 8. Creationist and Anti-Creationist Order Constructs -- Chapter 9. Creationist and Anti-Creationist Subject Constructs -- Chapter 10. Conclusion.
Keywords: Religion and sociology; Ethnology -- America; Culture; Religion; Sociology of Religion; American Culture; Religion